Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai PT BPR Kartasura Saribumi Cabang Masaran - Trisnowati, Juni (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2013)
This study analyzes the influence of motivation and discipline to the performance of employees of PT BPR Kartasura Saribumi Cabang Masaran.  The problems are formulated is: is  there  asignificant relationship  between motivation and  discipline to  employee performance either  partially  or simultaneously.  The  hypothesis  is "suspected  of motivation and  discipline has  a  significant  influence on  the performance  of employees of PT BPR Kartasura Saribumi Cabang Masaran either  partially or simultaneously".  Data collected primary  data obtained through  a  questionnaire given  to the  respondent,  and the number  of respondents as  many  as  14 employees. The  analysis includes  the coefficient of determination,  multiple  linear regression analysis,  t testand  F  test. Results  showed that the proposed  hypothesis accepted  as  true,  which  means  that there  is  asignificant influence either partially  or simultaneously between motivation and  discipline to  the performance of employees of PT BPR Kartasura Saribumi Cabang Masaran.Keywords: motivation, work discipline and employee performance